Public administration in India the higher civil service - Maheshwari, Shriram (New Delhi ; Oxford : Oxford University Press, 2005)
This book is about public administration in India, which is often synonymous with the role and performance of the Indian Administrative Service (IAS). The author stresses the indispensability of the civil service in a democratic polity like India and the decisive role it plays in assisting with the social and economic development of the country.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Civil Service -- India; Public administration -- India